2017
DOI: 10.1186/s13071-017-2175-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Multilocus Sequence Typing (MLST) scheme for Leishmania (Viannia) braziliensis and Leishmania (Viannia) panamensis in Colombia

Abstract: BackgroundLeishmaniases are parasitic vector-borne diseases affecting more than 12 million people in 98 countries. In Colombia, leishmaniasis is widespread and the most common clinical manifestation is cutaneous, mainly caused by L. panamensis and L. braziliensis. Currently, the genetic diversity of these species in Colombia is unknown. To address this, we applied molecular techniques for their characterization, using multilocus sequence typing (MLST) to explore the genetic variability and phylodynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…Likewise, the great diversity of circulating Leishmania species in Colombia plays a fundamental role in the permanence and propagation of the disease, given that neither epidemiological surveillance, nor treatment, take this variable into account. This assumes that all species are equally susceptible to treatment, which has been refuted in multiple studies [ 4 , 11 , 33 35 ]. The presence of some vectors in over half of the departments in Colombia ( Fig 5 ) shows the importance of this factor in the perpetuation of the epidemiological cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the great diversity of circulating Leishmania species in Colombia plays a fundamental role in the permanence and propagation of the disease, given that neither epidemiological surveillance, nor treatment, take this variable into account. This assumes that all species are equally susceptible to treatment, which has been refuted in multiple studies [ 4 , 11 , 33 35 ]. The presence of some vectors in over half of the departments in Colombia ( Fig 5 ) shows the importance of this factor in the perpetuation of the epidemiological cycle.…”
Section: Discussionmentioning
confidence: 99%
“…equatoriensis , L . naiffi ), and that the most prevalent species exhibit high genetic diversity [ 9 11 ]. This set of conditions conspires to produce an incidence of 33.6 per 100,000 inhabitants in 2015, leading to the categorization of the country as one of Intense Transmission by the Panamerican Health Organization (PAHO) according to its Leishmaniasis Compound Index [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reported studies so far have focused on L. braziliensis, where the majority report consistent findings in describing its high intraspecific genetic diversity [16,26,43] even in cell populations isolated from a single L. braziliensis strain ("sub-strain") [44], while in L. panamensis the results are not yet concordant, probably for the molecular approaches used. While studies using MLST reveal extreme genetic homogeneity within L. panamensis [10], others using MLEE [5], sequencing of specific genes (Cytb/HSP70) [6], AFLP [13], or microsatellites [14], have reported a high intraspecific genetic diversity in this species. Considering that DNA high-throughput sequencing has the potential to identify changes in the whole genome structure, we used this approach to reveal the intraspecific genomic variability of L. panamensis from Colombian clinical isolates and Panamanian genomes retrieved from databases.…”
Section: Discussionmentioning
confidence: 94%
“…Several nuclear and mitochondrial DNA markers (cytochrome b, COII, gp63, 18S-rRNA, mini-exon, HSP-70, and ribosomal internal transcribed spacer regions (ITS-rDNA)) as well as different molecular techniques such as polymerase chain reaction (PCR) [9], multilocus sequence typing (MLST) [10], multilocus enzyme electrophoresis (MLEE) [5,11], random amplified polymorphism (RAPD) [12], amplified fragment length polymorphisms (AFLP) [13] and microsatellites [14], have been used to evaluate the inter and intraspecific genetic variability of different Leishmania species (L. tropica, L. major, L. donovani, L. braziliensis, L. peruviana, L. guyanensis, and L. panamensis) [13][14][15][16][17][18][19]. However, the identification of such genetic variants across the whole genome has become possible only with the arrival of DNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was also shown that strains classified as different zymodemes can present the same genotype [ 18 , 20 ]. However, the low number of typed strains and the lack of consensus on the marker genes, as well as the lack of MLST database for Leishmania , have hindered the implementation of MLST as a reference typing method [ 22 ]. Until now, most of the epidemiological data available in the literature is based on MLEE classification, and many DNA-based typing methods correlate data with existing MLEE classification [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%